Composite microspheres, preparation method and application thereof, and purification method of urokinase

By using a modified composite microsphere chromatography column packing material of nano-iron oxide, polylactic acid, polylysine and arginine, the problem of insufficient adsorption capacity and activity in the removal of endotoxins from urokinase was solved, achieving more efficient endotoxin removal and enhanced urokinase activity.

CN120205119BActive Publication Date: 2025-11-21HUBEI RENFU EUREKA BIOTECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510374081.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-03-27
Publication Date
2025-11-21
Estimated Expiration
2045-03-27

AI Technical Summary

Technical Problem

In existing methods for removing endotoxins from urokinase, the adsorption capacity and urokinase activity still need further improvement, posing safety risks.

Method used

Modified nano-ferric oxide, polylactic acid, polylysine and arginine composite microspheres were used as chromatography column packing material. By adjusting conditions such as pH and temperature, the adsorption capacity for endotoxins and the activity of urokinase were improved.

Benefits of technology

It significantly improved the adsorption capacity and activity of endotoxin in urokinase, ensuring the purification effect of urokinase and patient safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application provides a composite microsphere, a preparation method and application thereof, and a method for purifying urokinase, and belongs to the fields of bioengineering and chemical engineering.The raw material of the composite microsphere comprises modified nanometer ferroferric oxide, polylactic acid, polylysine and arginine.The composite microsphere comprising the modified nanometer ferroferric oxide, the polylactic acid, the polylysine and the arginine is used as a chromatographic column filler, and a chromatographic column is carried out on a urokinase raw material solution, so that the adsorption capacity for endotoxin can be effectively improved, and the activity of the urokinase is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the fields of bioengineering and chemical engineering, specifically relating to a composite microsphere, its preparation method, its application, and a method for purifying urokinase. Background Technology

[0002] The importance of preventing death from thrombotic vascular diseases is increasing, and plasminogen activators, as an important class of cardiovascular drugs, have wide applications. Urokinase, an effective plasminogen activator extracted from fresh human urine, is an important thrombolytic drug, clinically used for thrombolytic therapy of pulmonary embolism, acute myocardial infarction, and peripheral thromboembolic diseases. Urokinase also inhibits the production of coagulation factors, thus exhibiting good thrombolytic and antithrombotic effects.

[0003] As an injectable drug, urokinase has strict requirements regarding endotoxin levels in its finished product, as these levels are crucial for patient safety. Endotoxins are components of the cell walls of Gram-negative bacteria and are released when bacteria die. The presence of endotoxins in injectable urokinase can trigger serious adverse reactions, such as endotoxic shock and disseminated intravascular coagulation, threatening patients' lives. Therefore, effective removal of endotoxins is essential during the production of urokinase raw materials to ensure safe use by patients.

[0004] The invention patent with publication number CN115449515A discloses a method for producing urokinase based on endotoxin removal, including the following steps: (1) sample pretreatment; (2) chromatography column preparation and packing: water is added to the composite microspheres to obtain a suspension, which is then packed into the column to obtain a chromatography column; the composite microspheres are composed of nano-iron oxide, polystyrene, and polylysine; (3) disinfection: the chromatography column and chromatography system are disinfected, and endotoxin is detected, with a negative result; (4) sample loading: the collected liquid is the urokinase raw material solution with endotoxin removed. This method utilizes the composite microspheres composed of nano-iron oxide, polystyrene, and polylysine to achieve rapid and efficient adsorption of endotoxin, effectively removing endotoxin from urokinase, but the adsorption capacity and urokinase activity still need to be further improved.

[0005] Chinese patent application CN111778232A discloses a method for removing endotoxins during the purification of human urokinase raw materials. The method includes the following steps: (1) sample pretreatment; (2) column preparation and packing; and (3) sterilization and sample loading. The column uses polymer anion exchange chromatography packing material, specifically Chromalite MQ / F weak-base anion exchange resin from Purolite Resins Ltd. (UK), TOYOPEARL ion exchange resin superQ-650M from Tosoh Corporation (Japan), or SOURCE 30Q high-speed low-reverse-pressure ion exchange medium from General Electric Company (USA). This method effectively removes endotoxins from urokinase intermediates by using polymer anion exchange chromatography medium and optimizing various process conditions, achieving a urokinase activity yield of 76-81%. However, the adsorption capacity and urokinase activity still need further improvement.

[0006] The conference paper (Preparation of polymer microspheres with functionalized surfaces and their application in endotoxin removal materials, Guo Jinshan) utilizes the functional groups on the surface of functionalized microspheres to perform a surface grafting reaction, grafting polylysine, which can adsorb endotoxins, and polyethylene glycol, which resists protein adsorption, onto the surface of the microspheres to obtain modified microspheres. The modified microspheres are expected to be used as selective adsorption materials for endotoxins in protein solutions; however, no experimental verification has been conducted.

[0007] Further research is needed to address the above issues and find ways to remove endotoxins from urokinase. Summary of the Invention

[0008] This invention addresses the problems existing in the prior art by providing a composite microsphere, its preparation method, and its application. The invention uses composite microspheres comprising modified nano-ferric oxide, polylactic acid, polylysine, and arginine as the packing material for chromatography column chromatography of urokinase raw material solutions, which can effectively improve the adsorption capacity for endotoxins and enhance the activity of urokinase.

[0009] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0010] In a first aspect, the present invention provides a composite microsphere, the raw materials of which include modified nano-ferric oxide, polylactic acid, polylysine and arginine.

[0011] Preferably, the mass ratio of the modified nano-ferric oxide, polylactic acid, polylysine and arginine is 1-3:10-20:2-4:1-3.

[0012] More preferably, the mass ratio of the modified nano-ferric oxide, polylactic acid, polylysine and arginine is 2:16:3:3.

[0013] Preferably, the modified nano-ferric oxide is prepared by modifying the nano-ferric oxide with a silane coupling agent.

[0014] Preferably, the silane coupling agent is 3-aminopropyltriethoxysilane.

[0015] More preferably, the modified nano-ferric oxide is prepared by:

[0016] Nano-iron oxide was dispersed in water, and 3-aminopropyltriethoxysilane was added and stirred to react. The mass ratio of nano-iron oxide to 3-aminopropyltriethoxysilane was 200-400:1. The reaction temperature was 50-60℃ and the reaction time was 10-15h. After the reaction was completed, the mixture was cooled, washed, and dried to obtain modified nano-iron oxide.

[0017] Preferably, the particle size of the nano-ferric oxide is 100-200 nm.

[0018] Secondly, the present invention provides a method for preparing the above-mentioned composite microspheres, comprising the following steps:

[0019] S1: Modified nano-ferric oxide and calcium phosphate are dispersed in water to obtain a dispersion;

[0020] S2: Add polylactic acid to the dispersion, control the stirring speed at 100-200 rpm, the temperature at 45-60℃, and adjust the pH to 8-12; after heating to 80-100℃, react for 2-4 hours, filter, wash, and obtain modified nano-iron tetraoxide-polylactic acid microspheres.

[0021] S3: Add polylysine to the arginine solution to obtain an amino acid mixture solution;

[0022] S4: The modified nano-iron tetroxide-polylactic acid microspheres were placed in an amino acid mixed solution, the pH was adjusted to 8-12, and the reaction was carried out overnight at 50-55℃ with shaking. After the reaction was completed, the mixture was filtered, washed until neutral, and dried to obtain the composite microspheres.

[0023] Preferably, in step S1, the mass ratio of the modified nano-ferric oxide to calcium phosphate is 1.5-3:1;

[0024] Preferably, in step S1, the concentration of the dispersion is 6-15%.

[0025] Preferably, in step S2, the molecular weight of the polylactic acid is 4000-5000;

[0026] Preferably, in step S2, the polylactic acid is a polylactic acid solution, the solvent is dichloromethane, and the concentration is 45-50 mg / mL.

[0027] Preferably, in step S3, the solvent of the amino acid mixed solution is a sodium carbonate aqueous solution with a mass fraction of 5-8%.

[0028] Thirdly, the present invention provides the application of the above-described composite microspheres in the purification of urokinase.

[0029] Preferably, the purified urokinase comprises adsorbing endotoxins from the urokinase.

[0030] Fourthly, the present invention provides a method for purifying urokinase, using the aforementioned composite microspheres, comprising the following steps:

[0031] 1) Sample pretreatment: Adjust the pH and conductivity of the urokinase raw material solution to obtain the sample solution;

[0032] 2) Preparation of chromatography column: Using composite microspheres as column chromatography packing material, water is added to the column chromatography packing material to obtain a suspension, which is then packed into the column to obtain a chromatography column;

[0033] The composite microspheres include modified nano-ferric oxide, polylactic acid, polylysine, and arginine;

[0034] 3) Disinfection: The chromatography column and chromatography system were disinfected, and endotoxin was tested; the result was negative.

[0035] 4) Sample purification: Equilibrate the chromatography column with equilibration buffer. After the UV, conductivity and pH are stable, load the sample. The sample to be loaded is the sample solution obtained in step 1). When the UV absorption of the flow-through peak is detected to be >50mAU, start collecting the flow-through liquid. After the sample loading is completed, continue to wash the chromatography column with equilibration buffer until the system detects UV absorption <50mAU, then stop collecting. The collected liquid is the urokinase raw material solution with endotoxin removed.

[0036] Preferably, in step 1), the pH of the urokinase raw material solution is 8-12, more preferably 1-11; and the conductivity is 3-6 ms / cm, more preferably 4 ms / cm.

[0037] Compared with the prior art, the present invention has the following beneficial effects: The present invention uses a composite microsphere comprising modified nano-iron oxide, polylactic acid, polylysine and arginine as a chromatography column packing material to perform chromatography on urokinase raw material solution, which can effectively improve the adsorption capacity for endotoxins, improve the activity of urokinase, and significantly increase the content of high molecular weight urokinase in the purified urokinase. Detailed Implementation

[0038] It is worth noting that, unless otherwise specified, the raw materials used in this invention are all commercially available products, and their sources are not specifically limited.

[0039] The following sources of raw materials are provided as examples:

[0040] Nano-iron oxide (50nm particle size): Produced by Zhejiang Manli Nanoparticles Co., Ltd.;

[0041] Nano-iron oxide (100nm particle size): Produced by Zhejiang Manli Nanoparticles Co., Ltd.

[0042] Nano-iron oxide (particle size 200nm): Produced by Zhejiang Manli Nanoparticles Co., Ltd.

[0043] Polylactic acid: Wuhan Kemic Biomedical Technology Co., Ltd., CAS: 26100-51-6, molecular weight is 5000.

[0044] Example 1

[0045] The preparation method of composite microspheres includes the following steps:

[0046] S1: Nano-iron oxide (particle size 100nm) was dispersed in water to obtain a nano-iron oxide solution with a concentration of 5mg / mL. 3-aminopropyltriethoxysilane was added and stirred to react. The mass ratio of nano-iron oxide to 3-aminopropyltriethoxysilane was 300:1. The reaction temperature was 55℃ and the reaction time was 13h. After the reaction was completed, the mixture was cooled, washed, and dried to obtain modified nano-iron oxide.

[0047] Modified nano-iron oxide (particle size 100nm) and calcium phosphate with a mass ratio of 2:1 were dispersed in water and ultrasonically dispersed at 100W for 10min to obtain a dispersion with a mass fraction of 8%.

[0048] S2: Dissolve polylactic acid in dichloromethane to prepare a polylactic acid solution with a concentration of 50 mg / mL;

[0049] S3: The polylactic acid solution was added dropwise to the dispersion and stirred to react. The mass ratio of modified nano-iron oxide to polylactic acid was 2:15. The stirring speed was 500 rpm. The pH was adjusted to 10. After the addition was completed, the mixture was reacted at 45℃ for 1.5 h. Then, the temperature was raised to 80-90℃ and reacted for 2 h. The mixture was then filtered and washed to obtain modified nano-iron oxide-polylactic acid microspheres.

[0050] S4: Add polylysine to the arginine solution, with a mass ratio of polylysine to arginine of 3:2, to obtain an amino acid mixed solution (the solvent is a 6% sodium carbonate aqueous solution by mass).

[0051] S5: The modified nano-iron oxide-polylactic acid microspheres were placed in an amino acid mixed solution with the mass ratio of modified nano-iron oxide, polylactic acid, polylysine and arginine being 2:15:3:2. The pH was adjusted to 10, and the mixture was shaken and reacted overnight at 50°C. After the reaction was completed, the mixture was filtered, washed until neutral, and dried to obtain composite microspheres.

[0052] Example 2

[0053] The preparation method of composite microspheres includes the following steps:

[0054] S1: Nano-iron oxide (particle size 100nm) was dispersed in water to obtain a nano-iron oxide solution with a concentration of 5mg / mL. 3-aminopropyltriethoxysilane was added and stirred to react. The mass ratio of nano-iron oxide to 3-aminopropyltriethoxysilane was 300:1. The reaction temperature was 55℃ and the reaction time was 13h. After the reaction was completed, the mixture was cooled, washed, and dried to obtain modified nano-iron oxide.

[0055] Modified nano-iron oxide (particle size 100nm) and calcium phosphate with a mass ratio of 2:1 were dispersed in water and ultrasonically dispersed at 100W for 10min to obtain a dispersion with a mass fraction of 8%.

[0056] S2: Polylactic acid was dissolved in dichloromethane to prepare a 50 mg / mL polylactic acid solution;

[0057] S3: The polylactic acid solution was added dropwise to the dispersion, and the mixture was stirred to react. The mass ratio of the modified nano-iron oxide to polylactic acid was 1:20. The stirring speed was 500 rpm, and the pH was adjusted to 10. After the addition was completed, the mixture was reacted at 45℃ for 1.5 h, and then the temperature was raised to 80-90℃ and reacted for 2 h. The mixture was then filtered, washed, and the modified nano-iron oxide-polylactic acid microspheres were obtained.

[0058] S4: Add polylysine to the arginine solution, with a mass ratio of polylysine to arginine of 2:3, to obtain an amino acid mixed solution (the solvent is a 6% sodium carbonate aqueous solution by mass).

[0059] S5: The modified nano-iron oxide-polylactic acid microspheres were placed in an amino acid mixed solution. The mass ratio of the modified nano-iron oxide, polylactic acid, polylysine and arginine was 1:20:2:3. The pH was adjusted to 10, and the mixture was shaken and reacted overnight at 50°C. After the reaction was completed, the mixture was filtered, washed until neutral, and dried to obtain the composite microspheres.

[0060] Example 3

[0061] The preparation method of composite microspheres includes the following steps:

[0062] S1: Nano-iron oxide (particle size 100nm) was dispersed in water to obtain a nano-iron oxide solution with a concentration of 5mg / mL. 3-aminopropyltriethoxysilane was added and stirred to react. The mass ratio of nano-iron oxide to 3-aminopropyltriethoxysilane was 300:1. The reaction temperature was 55℃ and the reaction time was 13h. After the reaction was completed, the mixture was cooled, washed, and dried to obtain modified nano-iron oxide.

[0063] Modified 2:1 nano-iron oxide (particle size 100nm) and calcium phosphate were dispersed in water and ultrasonically dispersed at 100W for 10min to obtain a dispersion with a mass fraction of 8%.

[0064] S2: Polylactic acid was dissolved in dichloromethane to prepare a 50 mg / mL polylactic acid solution;

[0065] S3: Add polylactic acid solution to dispersion and stir to react. The mass ratio of modified nano-iron oxide to polylactic acid is 3:10. The stirring speed is 500 rpm. Adjust the pH to 10. After the addition is complete, react at 45℃ for 1.5 h. Then raise the temperature to 80-90℃ and react for 2 h. Filter and wash to obtain modified nano-iron oxide-polylactic acid microspheres.

[0066] S4: Add polylysine to the arginine solution, with a mass ratio of polylysine to arginine of 4:1.

[0067] A mixed amino acid solution was obtained (the solvent was a 6% sodium carbonate aqueous solution by mass).

[0068] S5: The modified nano-iron oxide-polylactic acid microspheres were placed in an amino acid mixed solution with the mass ratio of modified nano-iron oxide, polylactic acid, polylysine and arginine being 3:10:4:1. The pH was adjusted to 10, and the mixture was shaken and reacted overnight at 50°C. After the reaction was completed, the mixture was filtered, washed until neutral, and dried to obtain composite microspheres.

[0069] Example 4

[0070] The preparation method of composite microspheres includes the following steps:

[0071] S1: Nano-iron oxide (particle size 200nm) was dispersed in water to obtain a nano-iron oxide solution with a concentration of 5mg / mL. 3-aminopropyltriethoxysilane was added and stirred to react. The mass ratio of nano-iron oxide to 3-aminopropyltriethoxysilane was 300:1. The reaction temperature was 55℃ and the reaction time was 13h. After the reaction was completed, the mixture was cooled, washed, and dried to obtain modified nano-iron oxide.

[0072] Modified nano-iron oxide (particle size 200nm) and calcium phosphate with a mass ratio of 2:1 were dispersed in water and ultrasonically dispersed at 100W for 10min to obtain a dispersion with a mass fraction of 8%.

[0073] S2: Polylactic acid was dissolved in dichloromethane to prepare a 50 mg / mL polylactic acid solution;

[0074] S3: The polylactic acid solution was added dropwise to the dispersion and stirred to react. The mass ratio of modified nano-iron oxide to polylactic acid was 2:15. The stirring speed was 500 rpm. The pH was adjusted to 10. After the addition was completed, the mixture was reacted at 45℃ for 1.5 h. Then, the temperature was raised to 80-90℃ and reacted for 2 h. The mixture was then filtered and washed to obtain modified nano-iron oxide-polylactic acid microspheres.

[0075] S4: Add polylysine to the arginine solution, with a mass ratio of polylysine to arginine of 3:2.

[0076] A mixed amino acid solution was obtained (the solvent was a 6% sodium carbonate aqueous solution by mass).

[0077] S5: The modified nano-iron oxide-polylactic acid microspheres were placed in an amino acid mixed solution with the mass ratio of modified nano-iron oxide, polylactic acid, polylysine and arginine being 2:15:3:2. The pH was adjusted to 10, and the mixture was shaken and reacted overnight at 50°C. After the reaction was completed, the mixture was filtered, washed until neutral, and dried to obtain composite microspheres.

[0078] Example 5

[0079] The preparation method of composite microspheres includes the following steps:

[0080] S1: Nano-iron oxide (particle size 100nm) was dispersed in water to obtain a nano-iron oxide solution with a concentration of 5mg / mL. 3-aminopropyltriethoxysilane was added and stirred to react. The mass ratio of nano-iron oxide to 3-aminopropyltriethoxysilane was 300:1. The reaction temperature was 55℃ and the reaction time was 13h. After the reaction was completed, the mixture was cooled, washed, and dried to obtain modified nano-iron oxide.

[0081] Modified nano-iron oxide (particle size 100nm) and calcium phosphate with a mass ratio of 1.5:1 were dispersed in water and ultrasonically dispersed at 100W for 10min to obtain a dispersion with a mass fraction of 8%.

[0082] S2: Polylactic acid was dissolved in dichloromethane to prepare a 50 mg / mL polylactic acid solution;

[0083] S3: The polylactic acid solution was added dropwise to the dispersion and stirred to react. The mass ratio of modified nano-iron oxide to polylactic acid was 2:15. The stirring speed was 500 rpm. The pH was adjusted to 10. After the addition was completed, the mixture was reacted at 45℃ for 1.5 h. Then, the temperature was raised to 80-90℃ and reacted for 2 h. The mixture was then filtered and washed to obtain modified nano-iron oxide-polylactic acid microspheres.

[0084] S4: Add polylysine to the arginine solution, with a mass ratio of polylysine to arginine of 3:2.

[0085] A mixed amino acid solution was obtained (the solvent was a 6% sodium carbonate aqueous solution by mass).

[0086] S5: The modified nano-iron oxide-polylactic acid microspheres were placed in an amino acid mixed solution with the mass ratio of modified nano-iron oxide, polylactic acid, polylysine and arginine being 2:15:3:2. The pH was adjusted to 10, and the mixture was shaken and reacted overnight at 50°C. After the reaction was completed, the mixture was filtered, washed until neutral, and dried to obtain composite microspheres.

[0087] Example 6

[0088] The preparation method of composite microspheres includes the following steps:

[0089] S1: Nano-iron oxide (particle size 100nm) was dispersed in water to obtain a nano-iron oxide solution with a concentration of 5mg / mL. 3-aminopropyltriethoxysilane was added and stirred to react. The mass ratio of nano-iron oxide to 3-aminopropyltriethoxysilane was 300:1. The reaction temperature was 55℃ and the reaction time was 13h. After the reaction was completed, the mixture was cooled, washed, and dried to obtain modified nano-iron oxide.

[0090] Modified nano-iron oxide (100 nm particle size) and calcium phosphate with a mass ratio of 3:1 were dispersed in water and ultrasonically dispersed at 100 W for 10 min to obtain a dispersion with a mass fraction of 8%.

[0091] S2: Polylactic acid was dissolved in dichloromethane to prepare a 50 mg / mL polylactic acid solution;

[0092] S3: The polylactic acid solution was added dropwise to the dispersion and stirred to react. The mass ratio of modified nano-iron oxide to polylactic acid was 2:15. The stirring speed was 500 rpm. The pH was adjusted to 10. After the addition was completed, the mixture was reacted at 45℃ for 1.5 h. Then, the temperature was raised to 80-90℃ and reacted for 2 h. The mixture was then filtered and washed to obtain modified nano-iron oxide-polylactic acid microspheres.

[0093] S4: Add polylysine to the arginine solution, with a mass ratio of polylysine to arginine of 3:2.

[0094] A mixed amino acid solution was obtained (the solvent was a 6% sodium carbonate aqueous solution by mass).

[0095] S5: The modified nano-iron oxide-polylactic acid microspheres were placed in an amino acid mixed solution with the mass ratio of modified nano-iron oxide, polylactic acid, polylysine and arginine being 2:15:3:2. The pH was adjusted to 10, and the mixture was shaken and reacted overnight at 50°C. After the reaction was completed, the mixture was filtered, washed until neutral, and dried to obtain composite microspheres.

[0096] Example 7

[0097] The preparation method of composite microspheres includes the following steps:

[0098] S1: Nano-iron oxide (particle size 100nm) was dispersed in water to obtain a nano-iron oxide solution with a concentration of 5mg / mL. 3-aminopropyltriethoxysilane was added and stirred to react. The mass ratio of nano-iron oxide to 3-aminopropyltriethoxysilane was 300:1. The reaction temperature was 55℃ and the reaction time was 13h. After the reaction was completed, the mixture was cooled, washed, and dried to obtain modified nano-iron oxide.

[0099] Modified nano-iron oxide (particle size 100nm) and calcium phosphate with a mass ratio of 2:1 were dispersed in water and ultrasonically dispersed at 100W for 10min to obtain a dispersion with a mass fraction of 8%.

[0100] S2: Polylactic acid was dissolved in dichloromethane to prepare a 50 mg / mL polylactic acid solution;

[0101] S3: The polylactic acid solution was added dropwise to the dispersion and stirred to react. The mass ratio of modified nano-iron oxide to polylactic acid was 2:15. The stirring speed was 500 rpm. The pH was adjusted to 10. After the addition was completed, the mixture was reacted at 45℃ for 1.5 h. Then, the temperature was raised to 80-90℃ and reacted for 2 h. The mixture was then filtered and washed to obtain modified nano-iron oxide-polylactic acid microspheres.

[0102] S4: Add polylysine to the arginine solution, with a mass ratio of polylysine to arginine of 3:2.

[0103] A mixed amino acid solution was obtained (the solvent was a 6% sodium carbonate aqueous solution by mass).

[0104] S5: The modified nano-iron oxide-polylactic acid microspheres were placed in an amino acid mixed solution with the mass ratio of modified nano-iron oxide, polylactic acid, polylysine and arginine being 1:10:2:1. The pH was adjusted to 10, and the mixture was shaken and reacted overnight at 50°C. After the reaction was completed, the mixture was filtered, washed until neutral, and dried to obtain composite microspheres.

[0105] Example 8

[0106] The preparation method of composite microspheres includes the following steps:

[0107] S1: Nano-iron oxide (particle size 100nm) was dispersed in water to obtain a nano-iron oxide solution with a concentration of 5mg / mL. 3-aminopropyltriethoxysilane was added and stirred to react. The mass ratio of nano-iron oxide to 3-aminopropyltriethoxysilane was 300:1. The reaction temperature was 55℃ and the reaction time was 13h. After the reaction was completed, the mixture was cooled, washed, and dried to obtain modified nano-iron oxide.

[0108] Modified nano-iron oxide (particle size 100nm) and calcium phosphate with a mass ratio of 2:1 were dispersed in water and ultrasonically dispersed at 100W for 10min to obtain a dispersion with a mass fraction of 8%.

[0109] S2: Polylactic acid was dissolved in dichloromethane to prepare a 50 mg / mL polylactic acid solution;

[0110] S3: The polylactic acid solution was added dropwise to the dispersion and stirred to react. The mass ratio of modified nano-iron oxide to polylactic acid was 2:15. The stirring speed was 500 rpm. The pH was adjusted to 10. After the addition was completed, the mixture was reacted at 45℃ for 1.5 h. Then, the temperature was raised to 80-90℃ and reacted for 2 h. The mixture was then filtered and washed to obtain modified nano-iron oxide-polylactic acid microspheres.

[0111] S4: Add polylysine to the arginine solution, with a mass ratio of polylysine to arginine of 3:2.

[0112] A mixed amino acid solution was obtained (the solvent was a 6% sodium carbonate aqueous solution by mass).

[0113] S5: The modified nano-iron oxide-polylactic acid microspheres were placed in an amino acid mixed solution with the mass ratio of modified nano-iron oxide, polylactic acid, polylysine and arginine being 3:20:4:3. The pH was adjusted to 10, and the mixture was shaken and reacted overnight at 50°C. After the reaction was completed, the mixture was filtered, washed until neutral, and dried to obtain composite microspheres.

[0114] Example 9

[0115] The preparation method of composite microspheres includes the following steps:

[0116] S1: Nano-iron oxide (particle size 100nm) was dispersed in water to obtain a nano-iron oxide solution with a concentration of 5mg / mL. 3-aminopropyltriethoxysilane was added and stirred to react. The mass ratio of nano-iron oxide to 3-aminopropyltriethoxysilane was 200:1. The reaction temperature was 55℃ and the reaction time was 13h. After the reaction was completed, the mixture was cooled, washed, and dried to obtain modified nano-iron oxide.

[0117] Modified nano-iron oxide (particle size 100nm) and calcium phosphate with a mass ratio of 2:1 were dispersed in water and ultrasonically dispersed at 100W for 10min to obtain a dispersion with a mass fraction of 8%.

[0118] S2: Polylactic acid was dissolved in dichloromethane to prepare a 50 mg / mL polylactic acid solution;

[0119] S3: The polylactic acid solution was added dropwise to the dispersion and stirred to react. The mass ratio of modified nano-iron oxide to polylactic acid was 2:15. The stirring speed was 500 rpm. The pH was adjusted to 10. After the addition was completed, the mixture was reacted at 45℃ for 1.5 h. Then, the temperature was raised to 80-90℃ and reacted for 2 h. The mixture was then filtered and washed to obtain modified nano-iron oxide-polylactic acid microspheres.

[0120] S4: Add polylysine to the arginine solution, with a mass ratio of polylysine to arginine of 3:2.

[0121] A mixed amino acid solution was obtained (the solvent was a 6% sodium carbonate aqueous solution by mass).

[0122] S5: The modified nano-iron oxide-polylactic acid microspheres were placed in an amino acid mixed solution with the mass ratio of modified nano-iron oxide, polylactic acid, polylysine and arginine being 1:10:2:1. The pH was adjusted to 10, and the mixture was shaken and reacted overnight at 50°C. After the reaction was completed, the mixture was filtered, washed until neutral, and dried to obtain composite microspheres.

[0123] Example 10

[0124] The preparation method of composite microspheres includes the following steps:

[0125] S1: Nano-iron oxide (particle size 100nm) was dispersed in water to obtain a nano-iron oxide solution with a concentration of 5mg / mL. 3-aminopropyltriethoxysilane was added and stirred to react. The mass ratio of nano-iron oxide to 3-aminopropyltriethoxysilane was 400:1. The reaction temperature was 55℃ and the reaction time was 13h. After the reaction was completed, the mixture was cooled, washed, and dried to obtain modified nano-iron oxide.

[0126] Modified nano-iron oxide (particle size 100nm) and calcium phosphate with a mass ratio of 2:1 were dispersed in water and ultrasonically dispersed at 100W for 10min to obtain a dispersion with a mass fraction of 8%.

[0127] S2: Polylactic acid was dissolved in dichloromethane to prepare a 50 mg / mL polylactic acid solution;

[0128] S3: The polylactic acid solution was added dropwise to the dispersion and stirred to react. The mass ratio of modified nano-iron oxide to polylactic acid was 2:15. The stirring speed was 500 rpm. The pH was adjusted to 10. After the addition was completed, the mixture was reacted at 45℃ for 1.5 h. Then, the temperature was raised to 80-90℃ and reacted for 2 h. The mixture was then filtered and washed to obtain modified nano-iron oxide-polylactic acid microspheres.

[0129] S4: Add polylysine to the arginine solution, with a mass ratio of polylysine to arginine of 3:2.

[0130] A mixed amino acid solution was obtained (the solvent was a 6% sodium carbonate aqueous solution by mass).

[0131] S5: The modified nano-iron oxide-polylactic acid microspheres were placed in an amino acid mixed solution with the mass ratio of modified nano-iron oxide, polylactic acid, polylysine and arginine being 1:10:2:1. The pH was adjusted to 10, and the mixture was shaken and reacted overnight at 50°C. After the reaction was completed, the mixture was filtered, washed until neutral, and dried to obtain composite microspheres.

[0132] Example 11

[0133] The preparation method of composite microspheres includes the following steps:

[0134] S1: Nano-iron oxide (particle size 100nm) was dispersed in water to obtain a nano-iron oxide solution with a concentration of 5mg / mL. 3-aminopropyltriethoxysilane was added and stirred to react. The mass ratio of nano-iron oxide to 3-aminopropyltriethoxysilane was 300:1. The reaction temperature was 60℃ and the reaction time was 15h. After the reaction was completed, the mixture was cooled, washed, and dried to obtain modified nano-iron oxide.

[0135] Modified nano-iron oxide (particle size 100nm) and calcium phosphate with a mass ratio of 2:1 were dispersed in water and ultrasonically dispersed at 100W for 10min to obtain a dispersion with a mass fraction of 8%.

[0136] S2: Polylactic acid was dissolved in dichloromethane to prepare a 50 mg / mL polylactic acid solution;

[0137] S3: The polylactic acid solution was added dropwise to the dispersion and stirred to react. The mass ratio of modified nano-iron oxide to polylactic acid was 2:15. The stirring speed was 500 rpm. The pH was adjusted to 10. After the addition was completed, the mixture was reacted at 45℃ for 1.5 h. Then, the temperature was raised to 80-90℃ and reacted for 2 h. The mixture was then filtered and washed to obtain modified nano-iron oxide-polylactic acid microspheres.

[0138] S4: Add polylysine to the arginine solution, with a mass ratio of polylysine to arginine of 3:2.

[0139] A mixed amino acid solution was obtained (the solvent was a 6% sodium carbonate aqueous solution by mass).

[0140] S5: The modified nano-iron oxide-polylactic acid microspheres were placed in an amino acid mixed solution with the mass ratio of modified nano-iron oxide, polylactic acid, polylysine and arginine being 1:10:2:1. The pH was adjusted to 10, and the mixture was shaken and reacted overnight at 50°C. After the reaction was completed, the mixture was filtered, washed until neutral, and dried to obtain composite microspheres.

[0141] Example 12

[0142] The preparation method of composite microspheres includes the following steps:

[0143] S1: Nano-iron oxide (particle size 100nm) was dispersed in water to obtain a nano-iron oxide solution with a concentration of 5mg / mL. 3-aminopropyltriethoxysilane was added and stirred to react. The mass ratio of nano-iron oxide to 3-aminopropyltriethoxysilane was 300:1. The reaction temperature was 50℃ and the reaction time was 10h. After the reaction was completed, the mixture was cooled, washed, and dried to obtain modified nano-iron oxide.

[0144] Modified nano-iron oxide (particle size 100nm) and calcium phosphate with a mass ratio of 2:1 were dispersed in water and ultrasonically dispersed at 100W for 10min to obtain a dispersion with a mass fraction of 8%.

[0145] S2: Polylactic acid was dissolved in dichloromethane to prepare a 50 mg / mL polylactic acid solution;

[0146] S3: The polylactic acid solution was added dropwise to the dispersion and stirred to react. The mass ratio of modified nano-iron oxide to polylactic acid was 2:15. The stirring speed was 500 rpm. The pH was adjusted to 10. After the addition was completed, the mixture was reacted at 45℃ for 1.5 h. Then, the temperature was raised to 80-90℃ and reacted for 2 h. The mixture was then filtered and washed to obtain modified nano-iron oxide-polylactic acid microspheres.

[0147] S4: Add polylysine to the arginine solution, with a mass ratio of polylysine to arginine of 3:2.

[0148] A mixed amino acid solution was obtained (the solvent was a 6% sodium carbonate aqueous solution by mass).

[0149] S5: The modified nano-iron oxide-polylactic acid microspheres were placed in an amino acid mixed solution with the mass ratio of modified nano-iron oxide, polylactic acid, polylysine and arginine being 1:10:2:1. The pH was adjusted to 10, and the mixture was shaken and reacted overnight at 50°C. After the reaction was completed, the mixture was filtered, washed until neutral, and dried to obtain composite microspheres.

[0150] Comparative Example 1

[0151] The difference from Example 1 is that the particle size of the nano-iron oxide is 50 nm, while the rest is the same as in Example 1, resulting in composite microspheres.

[0152] Comparative Example 2

[0153] The difference from Example 1 is that the mass ratio of nano-iron oxide, polylactic acid, polylysine and arginine is 4:25:5:1, while the rest is the same as in Example 1, resulting in composite microspheres.

[0154] Comparative Example 3

[0155] The difference from Example 1 is that the mass ratio of nano-iron oxide, polylactic acid, polylysine and arginine is 1:8:1:2, while the rest is the same as in Example 1, resulting in composite microspheres.

[0156] Comparative Example 4

[0157] The difference from Example 1 is that polylysine is replaced with arginine in the same mass ratio, while the rest is the same as in Example 1, to obtain composite microspheres.

[0158] Comparative Example 5

[0159] The difference from Example 1 is that arginine is replaced with polylysine in the same mass ratio, while the rest is the same as in Example 1, to obtain composite microspheres.

[0160] Comparative Example 6

[0161] The difference from Example 1 is that unmodified nano-iron oxide was used, while everything else was the same as in Example 1, resulting in composite microspheres.

[0162] Comparative Example 7

[0163] The difference from Example 1 is that polylactic acid is replaced with an equal mass of polystyrene, while everything else is the same as in Example 1, resulting in composite microspheres.

[0164] Comparative Example 8

[0165] The difference from Example 1 is that the mass ratio of nano-iron oxide to 3-aminopropyltriethoxysilane is 180:1, while the rest is the same as in Example 1, resulting in composite microspheres.

[0166] Comparative Example 9

[0167] The difference from Example 1 is that the mass ratio of nano-iron oxide to 3-aminopropyltriethoxysilane is 500:1, while the rest is the same as in Example 1, resulting in composite microspheres.

[0168] Comparative Example 10

[0169] The difference from Example 1 is as follows:

[0170] In S1, nano-iron oxide (particle size 100 nm) was dispersed in water to obtain a nano-iron oxide solution with a concentration of 5 mg / mL. 3-aminopropyltriethoxysilane was added and stirred to react. The mass ratio of nano-iron oxide to 3-aminopropyltriethoxysilane was 300:1. The reaction temperature was 55 °C and the reaction time was 20 h. After the reaction was completed, the mixture was cooled, washed, and dried to obtain modified nano-iron oxide. Other steps were the same as in Example 1 to obtain composite microspheres.

[0171] Comparative Example 11

[0172] The difference from Example 1 is as follows:

[0173] In S1, nano-iron oxide (particle size 100 nm) was dispersed in water to obtain a nano-iron oxide solution with a concentration of 5 mg / mL. 3-aminopropyltriethoxysilane was added and stirred to react. The mass ratio of nano-iron oxide to 3-aminopropyltriethoxysilane was 300:1. The reaction temperature was 40 °C and the reaction time was 20 h. After the reaction was completed, the mixture was cooled, washed, and dried to obtain modified nano-iron oxide. Other steps were the same as in Example 1 to obtain composite microspheres.

[0174] Comparative Example 12

[0175] The difference from Example 1 is as follows:

[0176] In S1, nano-iron oxide (particle size 100 nm) was dispersed in water to obtain a nano-iron oxide solution with a concentration of 5 mg / mL. 3-aminopropyltriethoxysilane was added and stirred to react. The mass ratio of nano-iron oxide to 3-aminopropyltriethoxysilane was 300:1. The reaction temperature was 70 °C and the reaction time was 13 h. After the reaction was completed, the mixture was cooled, washed, and dried to obtain modified nano-iron oxide. Other steps were the same as in Example 1 to obtain composite microspheres.

[0177] Experimental Example 1

[0178] The composite microspheres prepared in Example 1 and Comparative Examples 1-12 were used as column chromatography packing materials. The urokinase raw material was crude human urokinase from the same batch (20240812). Urokinase purification was performed. The purification method for urokinase specifically includes the following steps:

[0179] 1) Sample pretreatment: Adjust the pH of the urokinase raw material solution to 10 and the conductivity to 3-6 ms / cm to obtain the sample solution;

[0180] 2) Preparation of chromatography column: Using composite microspheres as the column packing material, water is added to the column packing material to obtain a suspension, which is then packed into the column to obtain the chromatography column; the volume ratio of the column packing material to water is 1:0.7; the chromatography flow rate of the chromatography column is 70-90 cm / h;

[0181] 3) Disinfection: The chromatography column and chromatography system were disinfected, and endotoxin was tested; the result was negative.

[0182] 4) Sample purification: Equilibrate the chromatography column with phosphate buffer. The equilibration conditions are: the deviation of the UV level is <0.1 mAU, and the pH and conductivity are the same as those in step (1). After the UV, conductivity and pH are stable, load the sample. The sample to be loaded is the sample solution obtained in step 1). When the UV absorption of the flow-through peak is detected to be >50 mAU, start collecting the flow-through liquid. After the sample loading is completed, continue to rinse the chromatography column with equilibration buffer until the system detects UV absorption <50 mAU, then stop collecting. The collected liquid is the urokinase raw material solution with endotoxin removed.

[0183] The effects of different composite fillers on the adsorption of endotoxins and the activity of urokinase were investigated. The results are shown in Table 1. The detection method was based on Appendix XI E of the Chinese Pharmacopoeia (Part II), which describes the bacterial endotoxin test. The endotoxin content in the crude urokinase raw material was found to be 4.3 EU / 10,000 units.

[0184] Table 1. Effects of different composite fillers and different process parameters on the production method of urokinase

[0185] Table 1 continues.

[0186]

[0187] As shown in Table 1, different composite microspheres have a significant impact on the endotoxin content of urokinase. Compared with Comparative Examples 1-11, the composite microspheres prepared in Example 1 of this invention can significantly reduce the endotoxin content in urokinase. Different process parameters also affect the endotoxin content of urokinase.

[0188] Experimental Example 2

[0189] The composite microspheres prepared in Examples 1-12 and Comparative Examples 1-12 were used as column chromatography packing materials. The urokinase raw material was crude human urokinase from the same batch (20240812). Urokinase purification was performed. The purification method for urokinase specifically includes the following steps:

[0190] 1) Sample pretreatment: Adjust the pH of the urokinase raw material solution to 10 and the conductivity to 4 ms / cm to obtain the sample solution;

[0191] 2) Preparation of chromatography column: Using composite microspheres as the column packing material, water was added to the column packing material to obtain a suspension, which was then packed into the column to obtain the chromatography column; the volume ratio of the column packing material to water was 1:0.7; the chromatography flow rate of the column was 70 cm / h;

[0192] 3) Disinfection: The chromatography column and chromatography system were disinfected, and endotoxin was tested; the result was negative.

[0193] 4) Sample purification: The chromatography column was equilibrated with phosphate buffer. The equilibration conditions were: UV level deviation <0.1 mAU, pH and conductivity corresponding to those in step (1); after UV, conductivity and pH stabilized, the sample was loaded. The sample loaded was the sample solution obtained in step 1); when the UV absorption of the flow-through peak was detected to be >50 mAU, the flow-through liquid was collected. After the sample loading was completed, the chromatography column was rinsed with equilibration buffer until the system detected UV absorption <50 mAU, at which point the collection was stopped. The collected liquid was the urokinase raw material solution after endotoxin removal. The relative content of high molecular weight urokinase in urokinase was calculated in Examples 1-12 and Comparative Examples 1-11. The activity yield and specific activity of urokinase in each example were calculated according to the method described in Part I of the main text of the 2020 edition of the Chinese Pharmacopoeia. The results are shown in Table 2.

[0194] Table 2. Results

[0195]

[0196]

[0197] As shown in Table 2, compared with the comparative examples, the composite microspheres prepared in Examples 1-12 of this invention, after purifying urokinase, showed a significant increase in the relative content of high molecular weight urokinase, a significant increase in activity yield, and a significant increase in specific activity.

[0198] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, and is not intended to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions made by those skilled in the art to the technical solution of the present invention do not depart from the essence and scope of the technical solution of the present invention.

Claims

1. A composite microsphere, characterized in that, The raw materials contain modified nano-ferric oxide, polylactic acid, polylysine and arginine in a mass ratio of 1-3:10-20:2-4:1-3; The method for preparing the modified nano-ferric oxide is as follows: Nano-sized iron oxide (Fe3O4) was dispersed in water, and 3-aminopropyltriethoxysilane was added and stirred to react. The mass ratio of nano-sized iron oxide to 3-aminopropyltriethoxysilane was 200-400:

1. The reaction temperature was 50-60°C, and the reaction time was 10-15 h. After the reaction was completed, the mixture was cooled, washed, and dried to obtain modified nano-sized iron oxide. The particle size of the nano-sized iron oxide was 100-200 nm. The method for preparing the composite microspheres includes the following steps: S1: Modified nano-ferric oxide and calcium phosphate are dispersed in water to obtain a dispersion; S2: Add polylactic acid to the dispersion, control the stirring speed at 100-200 rpm, the temperature at 45-60℃, and adjust the pH to 8-12; after heating to 80-100℃, react for 2-4 hours, filter, wash, and obtain modified nano-iron tetraoxide-polylactic acid microspheres. S3: Add polylysine to the arginine solution to obtain an amino acid mixture solution; S4: The modified nano-iron tetroxide-polylactic acid microspheres were placed in an amino acid mixed solution, the pH was adjusted to 8-12, and the reaction was carried out overnight at 50-55℃ with shaking. After the reaction was completed, the mixture was filtered, washed until neutral, and dried to obtain the composite microspheres.

2. The method for preparing the composite microspheres according to claim 1, characterized in that, Includes the following steps: S1: Modified nano-ferric oxide and calcium phosphate are dispersed in water to obtain a dispersion; S2: Add polylactic acid to the dispersion, control the stirring speed at 100-200 rpm, the temperature at 45-60℃, and adjust the pH to 8-12; after heating to 80-100℃, react for 2-4 hours, filter, wash, and obtain modified nano-iron tetraoxide-polylactic acid microspheres. S3: Add polylysine to the arginine solution to obtain an amino acid mixture solution; S4: The modified nano-iron tetroxide-polylactic acid microspheres were placed in an amino acid mixed solution, the pH was adjusted to 8-12, and the reaction was carried out overnight at 50-55℃ with shaking. After the reaction was completed, the mixture was filtered, washed until neutral, and dried to obtain the composite microspheres.

3. The preparation method according to claim 2, characterized in that, In step S1, the mass ratio of the modified nano-ferric oxide to calcium phosphate is 1.5-3:1; the mass fraction of the dispersion is 6-15%.

4. The preparation method according to claim 2, characterized in that, In step S1, the mass fraction of the dispersion is 6-15%.

5. The use of the composite microspheres according to claim 1 in the purification of urokinase.

6. A method for purifying urokinase, characterized in that, Using the composite microspheres of claim 1, the steps include: 1) Sample pretreatment: Adjust the pH and conductivity of the urokinase raw material solution to obtain the sample solution; 2) Preparation of chromatography column: Using composite microspheres as column chromatography packing material, water is added to the column chromatography packing material to obtain a suspension, which is then packed into the column to obtain a chromatography column; The composite microspheres include modified nano-ferric oxide, polylactic acid, polylysine, and arginine; 3) Disinfection: The chromatography column and chromatography system were disinfected, and endotoxin was tested; the result was negative. 4) Sample purification: Equilibrate the chromatography column with equilibration buffer. After the UV, conductivity and pH are stable, load the sample. The sample to be loaded is the sample solution obtained in step 1). When the UV absorption of the flow-through peak is detected to be >50mAU, start collecting the flow-through liquid. After the sample loading is completed, continue to wash the chromatography column with equilibration buffer until the system detects UV absorption <50mAU, then stop collecting. The collected liquid is the urokinase raw material solution with endotoxin removed.

Citation Information

Patent Citations

  • Method for removing endotoxin in human urokinase raw material refining process

    CN111778232A

  • Magnetic platelet adsorption particle and preparation method thereof

    CN105203752A

  • Urokinase production method based on endotoxin removal

    CN115449515A